2000
DOI: 10.1021/jf0008487
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tea Catechins on the ERE-Regulated Estrogenic Activity

Abstract: Tea catechins exert many biological effects, including anticancer and antibacterial activities. Also, it is reported that some plant flavonoids exhibit estrogenic activity. In this study, we investigated estrogenic or antiestrogenic activities of catechins in HeLa cells transiently transfected with an estrogen response element (ERE)-regulated luciferase reporter and an estrogen receptor (ER) alpha or ERbeta expression vector. Catechins alone did not induce luciferase (luc) activity in either of the ERs. Additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
43
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 38 publications
3
43
0
Order By: Relevance
“…A study in postmenopausal Chinese women found that plasma estrone levels were significantly 19% higher in regular black tea drinkers than in nondrinkers of tea [15]. An in vitro study showed that in the presence of estrogen, tea catechins in high concentrations had antiestrogenic activities through ERa but estrogenic activities at lower concentrations [16]. This may suggest that high intakes of tea catechins may decrease the risk of breast cancer, whereas lower intakes may increase the risk.…”
Section: Discussionmentioning
confidence: 99%
“…A study in postmenopausal Chinese women found that plasma estrone levels were significantly 19% higher in regular black tea drinkers than in nondrinkers of tea [15]. An in vitro study showed that in the presence of estrogen, tea catechins in high concentrations had antiestrogenic activities through ERa but estrogenic activities at lower concentrations [16]. This may suggest that high intakes of tea catechins may decrease the risk of breast cancer, whereas lower intakes may increase the risk.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed that catechins, which are abundant in green teas, have cancer preventing effects [106,107]. These polyphenols were also demonstrated to modulate estrogen action through molecular mechanisms at the serum concentration after tea-drinking [108,109].…”
Section: Phytoestrogensmentioning
confidence: 99%
“…Previous studies demonstrated that high levels of estrogens were consistently associated with a high risk of gallbladder cancer in women (43)(44)(45). Experimental data from animal and cell models suggested that tea may affect estrogen metabolism, although the detailed mechanisms underlying this effect remain unknown (46,47).…”
Section: Discussionmentioning
confidence: 99%